ULF Waves Generated Near the Plasmapause by the Magnetosphere‐Ionosphere Interactions. Issue 2 (7th February 2020) - Streltsov, Anatoly V.; Mishin, Evgeny V.
Abstract: Ultralow frequency (ULF) electromagnetic waves are regularly detected by satellites near the plasmapause during substorms. Usually, the small‐scale waves are observed embedded in the large‐scale, quasi‐stationary electric field. We suggest that the small‐scale waves are generated in the ionosphere by the interactions between the large‐scale field and irregularities in the ionospheric density/conductivity. Under certain conditions, these waves can be trapped in the global magnetospheric resonator and amplified by the positive feedback interactions with the ionosphere. To verify this hypothesis, we model with a two‐fluid magnetohydrodynamics code structure and amplitude of the ULF waves simultaneously observed near the plasmapause by the Defense Meteorological Satellite Program satellite at low altitudes and the Combined Release and Radiation Effects satellite at high altitudes. Simulations reproduce in good, quantitative detail the structure and amplitude of the observed waves. In particular, simulations reproduce a "spiky" character of the electric field observed by the Defense Meteorological Satellite Program satellite at low altitude, which is a characteristic feature of ULF waves produced by the ionospheric feedback instability. Key Points: We model ULF waves observed by CRRES and DMSP satellites at different altitudes near the plasmapause Simulations confirm that these waves are generated by the feedback instability driven by the electric field in the ionosphere Single simulation reproduces structure and amplitude of the fields observed by both satellites